The Drive for Muscularity among Adolescent Boys: Its Relationship with Global Self-Esteem - Rasa Jankauskienė; Ramutis Kairaitis (Lithuanian Sports University, 2018)
Among adolescent boys a higher drive for muscularity is related with poorer self-esteem and more symptoms of depression. There is an agreement that male athletes, in general, experience greater body satisfaction compared to nonathletes of the same age, however there is lack of studies to demonstrate how participation in various sports relates in terms of drive for muscularity and global self-esteem among adolescent boys. One hundred adolescent boys (mean age - 14.63 ± 1.97) took part in the study. 29 boys were at 6 th  grade, 34 - at 8 th , and 37 - at 10 th  grade. All the participants completed the self-constructed questionnaire consisting of 21 items. The following blocks of questions or statements were included into the questionnaire: demographic variables (age, grade, the living place (urban or rural)), global self-esteem (Rosenberg's (1989) questionnaire of self-esteem), body esteem (the satisfaction with one's own appearance and appearance of various body parts), and involvement to after-school activities (involvement in activity (for at least half a year) was considered as formal belonging to a club, school, or group, but not independent activities at the leisure time). The participants also completed the questionnaire Drive for Muscularity Scale (DMS) (McCre- ary, Sasse, 2000). Results showed no signiﬁ cant differences in the drive for muscularity among the boys involved in different after-school activities, while the greatest drive was demonstrated by adolescents involved in dancing. The adolescents involved and not involved in sport did not show signiﬁ cant differences in global self-esteem and overall appearance evaluation while the lowest dissatisfaction was common to the boys involved in dancing. The drive for muscularity was not signiﬁ cantly related to poorer overall appearance evaluation and self-esteem among adolescent boys involved in various after-school activities. Involvement in sport activities might mediate the negative effect of the drive for muscularity. The drive for muscularity might also be closely related to the demands of sport activities, but not to the improvement of personal appearance. However, it was found that dissatisfaction with body image and weight was more closely related to low self-esteem among girls, but not among boys, so our study partially supported the previous ﬁ ndings. The future studies should investigate the drive for muscularity, body-esteem and self-esteem interrelation in the samples of adolescent boys involved in recreational and professional sport. Keywords: adolescent boys, drive for muscularity, self-esteem, afterschool activities.